Cinemagraph as a medium in enhancing the effectiveness of anti - smoking PSA campaigns / Fahmi Samsudin - Samsudin, Fahmi (2018)
Cinema graph is one of the new technology that involve moving images where the format is existence from the previous graphic interchange format (GIF) that delivers contents in interactivity and other elements which creates interaction. A quantitative method was utilized to test the reliability of this technique among respondents where the results demonstrated self-designed measure is a very much reliable instrument, while three factors emerged with high reliability scores of between .70 and above. Data analysis showed more than half of the respondents agreed on the technique of cinemograph and fully supported the implementation of technique in any types of advertising mediums. Findings from the results confirmed the technique of cinemograph influenced viewers due to the interactivity elements and the contents. This concluded that the technique can be proceed in the future of public service announcements campaign, and also could replace other types of media that traditionally printed such as poster and billboard advertisements. Thus, this can save huge amount of number in manpower as well as costing of printed production process. This research is hoped to assist the advertising industries in gaining new medium like cinema graph technique that not only rich in interactive elements, but also at the same time saving budget in the making process. Also, this research intended to develop the technique in higher level, where the technique can be used widely apply in the education system in which can act as a tool in the learning and teaching activities.